Characterization of AiiK, an AHL lactonase, from Kurthia huakui LAM0618T and its application in quorum quenching on Pseudomonas aeruginosa PAO1 - Weiwei Dong (Nature Portfolio, 2018)
Abstract N-Acyl homoserine lactones (AHLs) act as the key quorum sensing (QS) signal molecules in gram-negative bacteria, which coordinates gene expression and then activates various processes, including biofilm formation and production of virulence factors in some pathogens. Quorum quenching (QQ), which is the inactivation of the signal molecules by means of enzymatic degradation or modification, inhibits the processes of QS rather than killing the pathogens and is a promising antipathogenic strategy to control the bacterial pathogens. In this study, an AHL lactonase gene (named aiiK) was cloned from Kurthia huakuii LAM0618T and the AHL lactonase AiiK was expressed by Escherichia coli. AiiK exhibits a variable substrate spectrum and efficient degradation of the AHL compounds. The enzyme assays demonstrated that AiiK behaves as an AHL lactonase that can hydrolyze the lactone bond of the AHLs. The total hydrolytic efficiency of AiiK for C10-HSL is 3.9 s−1·mM−1. AiiK can also maintain 20% activity after 12 h incubation at 37 °C and demonstrate great resistance to α-chymotrypsin, trypsin, and protease K. Furthermore, AiiK significantly inhibits the biofilm formation and attenuates extracellular proteolytic activity and pyocyanin production of Pseudomonas aeruginosa PAO1, which indicates the potential application of AiiK as a biocontrol agent or an anti-pathogenic drug.